3D structure of lightweight, conductive cellulose nanofiber foam. (1st February 2021) - Lee, Hwarueon; Kim, Sunga; Shin, Sungchul; Hyun, Jinho
Highlights: CNF foam-based ink is prepared for direct ink writing 3D printing. Colloidal stability of the CNF liquid foam is achieved. Flexible design of CNF foam structures is enabled by 3D printing. Lightweight conductive CNF foams are prepared on a solid CNF foam. Abstract: We investigate the three-dimensional (3D) structuring of cellulose nanofiber (CNF) foam-based ink using direct ink writing 3D printing and the transformation of CNF foam from an insulator to a conductor. The colloidal stability of a CNF foam is critical to producing a solid CNF foam which can be used as a template for the synthesis of conducting polymers. Liquid CNF foam ink is produced by simple stirring of CNF suspension with sodium dodecyl sulfate as an emulsifier. The shear thinning behavior of the liquid CNF foam ink enables printing through a needle. Flexible design of CNF foam structures is enabled by 3D printing using computer-aided design. Lightweight conductive CNF foams are prepared via in situ polymerization of polypyrrole on a solid CNF foam. The topological features of the resultant porous conductive CNF foams are observed, and their conductivity is investigated.